2018
DOI: 10.1002/hast.808
|View full text |Cite
|
Sign up to set email alerts
|

Community Engagement and Field Trials of Genetically Modified Insects and Animals

Abstract: New techniques for the genetic modification of organisms are creating new strategies for addressing persistent public health challenges. For example, the company Oxitec has conducted field trials internationally—and has attempted to conduct field trials in the United States—of a genetically modified mosquito that can be used to control dengue, Zika, and some other mosquito‐borne diseases. In 2016, a report commissioned by the National Academies of Sciences, Engineering, and Medicine discussed the potential ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 44 publications
0
56
0
Order By: Relevance
“…While authors acknowledged that it would not be possible to seek consent from all humans who could potentially be impacted by the release of genome-edited mosquitoes, it was argued that release could nonetheless be justified if the public health benefits of the trial are important enough for the community [102]. It was suggested that one way to conduct field trials with genetically modified animals while respecting the interests of community members is to use community advisory boards and a community authority [107].…”
Section: Public Acceptabilitymentioning
confidence: 99%
“…While authors acknowledged that it would not be possible to seek consent from all humans who could potentially be impacted by the release of genome-edited mosquitoes, it was argued that release could nonetheless be justified if the public health benefits of the trial are important enough for the community [102]. It was suggested that one way to conduct field trials with genetically modified animals while respecting the interests of community members is to use community advisory boards and a community authority [107].…”
Section: Public Acceptabilitymentioning
confidence: 99%
“…9 Some ethicists have in fact proposed the use of mass consent forms in field trials. with GMOs, which have unforeseen impacts beyond the range of a given locale or population, since seeds, for example, can be disseminated by insects that travel widely, or by the wind.…”
Section: On the Notion Of Informed Consent And Some Of Its Contextsmentioning
confidence: 99%
“…As Carolyn Neuhaus has recently discussed, trials involving the release of genetically modified organisms such as insects or animals pose special difficulties here, since they tend to move beyond a given community, raising issues of who should be informed and how consent could be elicited. 9 Some ethicists have in fact proposed the use of mass consent forms in field trials. 10 But given the evident impracticality of securing such consent, what alternative procedures could respect the autonomy and dignity of people in such cases?…”
Section: On the Notion Of Informed Consent And Some Of Its Contextsmentioning
confidence: 99%
“…Still, there are problematic gaps in NASEM's recommendations that need to be carefully considered moving forward. For example, Neuhaus [2018] points out that the vagueness of the definition of 'community engagement' that so haunted the Oxitec trials in the Florida Keys, is not adequately resolved in NASEM's report. Moreover, NASEM's report "fails to acknowledge the strong commercial drivers that may bring gene drives into use" [Thomas, 2016, n.p.].…”
Section: Conclusion: Lessons For Crisprmentioning
confidence: 99%